2013
DOI: 10.1155/2013/964637
|View full text |Cite
|
Sign up to set email alerts
|

Ingestion of Leucine + Phenylalanine with Glucose Produces an Additive Effect on Serum Insulin but Less than Additive Effect on Plasma Glucose

Abstract: Most individual amino acids stimulate insulin secretion and attenuate the plasma glucose response when ingested with glucose. We determined whether ingestion of two amino acids simultaneously with glucose would result in an additive effect on the glucose area response compared with ingestion of amino acids individually. Leucine and phenylalanine were chosen because they were two of the most potent glucose-lowering amino acids when given individually. Eight healthy subjects were studied on four separate days. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…By considering the great immediate insulin concentration, we would have rather expected a decrease in amino acid absorption with the EMS diet compared to the control diet. In this regard, additive effects of glucose and single amino acid (leucine and phenylalanine) intake on serum insulin concentration have been reported in humans [ 45 ]. Both leucine and phenylalanine were among the amino acids which concentrations were elevated by EMS diet, and might have theoretically added to the present immediate insulin response after the meal.…”
Section: Discussionmentioning
confidence: 99%
“…By considering the great immediate insulin concentration, we would have rather expected a decrease in amino acid absorption with the EMS diet compared to the control diet. In this regard, additive effects of glucose and single amino acid (leucine and phenylalanine) intake on serum insulin concentration have been reported in humans [ 45 ]. Both leucine and phenylalanine were among the amino acids which concentrations were elevated by EMS diet, and might have theoretically added to the present immediate insulin response after the meal.…”
Section: Discussionmentioning
confidence: 99%
“…Dietary protein has been shown to have insulin stimulating effects [ 31 , 32 , 33 ]. In a mouse model study, it was demonstrated that the presence of amino acids and insulin triggered a greater uptake of glucose into muscle tissue than insulin alone [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Note that the intensity increase of the three peaks at 1004, 1030, and 1208 cm −1 assigned to phenylalanine (Phe) was also observed after differentiation, in which Phe is an important cell factor for inducing insulin generation. [31][32][33] In particular, an intensity increase of the peak at 1267 cm −1 , which was assigned to amide III and related to changes in protein secondary structure, 34 was observed after differentiation, indicating that the type of synthetic protein in the amide III region might be changed after differentiation. Importantly, the peak at 665 cm −1 assigned to DNA, as described in Refs.…”
Section: Raman Spectroscopy and Data Preprocessingmentioning
confidence: 96%